Combining carbon and oxygen isotopic signatures to identify ozone-induced declines in tree water-use efficiency. (2nd April 2021) - Li, Pin; Feng, Zhaozhong; Shang, Bo; Uddling, Johan
Abstract: Ground-level ozone (O3 ) pollution affects the plant carbon and water balance, but the relative contributions of impaired photosynthesis and the loss of stomatal functioning to the O3 -induced reductions in water-use efficiency (WUE) remain unclear. We combined the leaf stable dual isotopic signatures of carbon (δ 13 C) and oxygen (δ 18 O) with related instantaneous gas exchange performance to determine the effects of O3 dose on the net photosynthetic rate ( A n ), stomatal conductance ( g s ) and intrinsic WUE (iWUE = A n / g s ) in four tree species (one being a hybrid) exposed to five O3 levels. The iWUE declined for each step increase in O3 level, reflecting progressive loss of the coupling between leaf carbon gain and water loss. In ambient compared with charcoal-filtered air, the decreased iWUE was associated with reductions in both A n and g s (i.e., decreased δ 13 C and increased δ 18 O). In elevated O3 treatments, however, the iWUE declines were caused by reduced A n at constant or increased g s . The results show that the dual isotope approach provides a robust way to gather time-integrated information on how O3 pollution affects leaf gas exchange. Our study highlights that O3 -induced decoupling between photosynthesis and stomatal regulation causes large and progressive declines in the WUE of forest trees, demonstrating the need for incorporating this hitherto unaccounted for effect into vegetation models.